Consumer Perception Of Wardah Cosmetic Products: Persepsi Konsumen Terhadap Produk Kosmetik Wardah - Ervina Pujianingrum Supriyanto; Kukuh Sinduwiatmo Sinduwiatmo (Academia Open, 2021)
This study entitled "CONSUMER PERCEPTION OF WARDAH COSMETIC PRODUCTS" at the residents of RT 03 RW 01 Singopadu Village. The purpose of this study was to determine consumer perceptions of Wardah cosmetic products. Researchers used a qualitative descriptive research method. Data analysis in this study was carried out by analyzing according to Miles and Huberman, namely reducing data, presenting data and withdrawing verification. The results showed that the residents of RT 03 RW 01 Singopadu Village had a good perception of Wardah's cosmetic products. With the existence of halal certification, it strengthens the perception of individuals, especially Muslims. Not only from the halal certification, but because of the suitability of the skin type. Wardah's product quality is recognized as good because it is made from safe ingredients that have been tested by BPOM. Residents of RT 03 RW 01 Singopadu Village give positive perceptions of Wardah cosmetic products. But it comes back to individuals if they fit they will buy it. In accordance with Kotler's theory (2005) states that consumers have a perception of Wardah's products and are ready to make purchases or exchange between money and a promise to pay with the ownership rights of an item.